Flushing cows - R.R. Schalles; G. Kiracofe; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1976)
Starting to flush cows 95 days before the breeding season began significantly increase conception rate and required less total feed.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Flushing; Conception rate; Feed